Pantothenic acid ameliorates hepatic fibrosis by targeting IGFBP6 to regulate the TGF-β/SMADs pathway - Zhengxin Jin; Zhengsen Jin; Zeyu Liu; Yongcheng Yin; Yuchen Zhang; Ying Zhang; Jianning Kang; Yuepeng Fang; Wei Jiang; Bin Ning (Communications Biology)
Abstract Hepatic fibrosis progression involves complex multicellular crosstalk, highlighting the critical need to identify key therapeutic targets. In this study, we identify insulin-like growth factor binding protein 6 (IGFBP6) as a marker specifically enriched in hepatic stellate cells (HSCs) and upregulated in viral hepatitis-associated fibrosis. Using thioacetamide (TAA)-induced mouse models and transforming growth factor-β (TGF-β)-stimulated cell models, we demonstrate the pro-fibrotic role of IGFBP6. Through network pharmacology screening, pantothenic acid (PA) is identified as a potent compound targeting IGFBP6. PA administration significantly reduces collagen deposition, attenuates HSCs’ activation, and decreases hepatic fibrosis-related markers. Notably, PA maintains efficacy in mouse models with established fibrosis. Mechanistically, PA directly interacts with IGFBP6, inducing ubiquitin-dependent degradation and inhibiting TGF-β/SMADs signaling. This study identifies IGFBP6 as a driver of hepatic fibrosis and validates PA as a potent therapeutic agent. Therefore, targeting IGFBP6 with PA offers a potential clinical treatment strategy for hepatic fibrosis.